2014
DOI: 10.7861/clinmedicine.14-6-633
|View full text |Cite
|
Sign up to set email alerts
|

How do medical doctors in the European Union demonstrate that they continue to meet criteria for registration and licencing?

Abstract: This paper reviews procedures for ensuring that physicians in the European Union (EU) continue to meet criteria for registration and the implications of these procedures for cross-border movement of health professionals following implementation of the 2005/36/EC Directive on professional qualifi cations. A questionnaire was completed by key informants in 10 EU member states, supplemented by a review of peer-reviewed and grey literature and a review conducted by key experts in each country. The questionnaire co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…One study found that in certain countries (Spain, Austria, Finland and Estonia) there was an implicit expectation that doctors maintain competence without needing to comply with formal standards. Whereas in others (Belgium, Germany, Hungary, the Netherlands, Slovenia and the UK), an explicit demonstration of continued competence is mandatory [34]. Further, when representatives from 14 EU countries were surveyed, authors concluded that the systems of licensing and registration vary so much that it creates confusion and problems in the context of the free movement of doctors.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that in certain countries (Spain, Austria, Finland and Estonia) there was an implicit expectation that doctors maintain competence without needing to comply with formal standards. Whereas in others (Belgium, Germany, Hungary, the Netherlands, Slovenia and the UK), an explicit demonstration of continued competence is mandatory [34]. Further, when representatives from 14 EU countries were surveyed, authors concluded that the systems of licensing and registration vary so much that it creates confusion and problems in the context of the free movement of doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is interesting to consider possible pathways towards ensuring more affirmative approaches to physicians' competence to practise, with the intention of improving patient safety and quality of care in the future. Previous work 8 has shown that no uniform approach to actively maintaining competence could be identified among participating member states. However, CPD and CME are generally recognised as key requirements for maintaining professional standards.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of a series exploring professional standards across Europe and builds on earlier papers on licensing and registration processes 7 and mechanisms to maintain professional competence. 8…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, despite countries adopting recertification or re‐licensure of doctors, the PPI element in these processes is seldom reported in the academic literature. For example, in Belgium, evidence for continuing medical education (CME) involves a review of complaints or compliments . The College of Physicians and Surgeons of Alberta, Canada, the statutory medical registration body for the province, has adopted a multi‐source feedback (MSF) system for all physicians/surgeons in its jurisdiction .…”
Section: Introductionmentioning
confidence: 99%